Metabolic Dysfunction-Associated Steatotic Liver Disease (MASLD): Evolving Insights into Pathogenesis, Progression, and Personalized Treatment Approaches - Kukiełka, Paweł; Moliszewska , Katarzyna; Kośka , Joanna; Dywan , Kacper; Błaszkiewicz , Michał; Mazurek , Julia; Załęcka , Julia; Nowik , Alicja; Musiorska , Martyna; Łocik , Gabriela (Quality in Sport, 2025)
Background: Metabolic Dysfunction-Associated Steatotic Liver Disease (MASLD), previously classified under non-alcoholic fatty liver disease (NAFLD), is an increasingly prevalent chronic liver disorder tightly linked to obesity, insulin resistance, and systemic metabolic dysfunction. It ranges from simple steatosis to nonalcoholic steatohepatitis (MASH), fibrosis, cirrhosis, and hepatocellular carcinoma. Objective: This review explores the current understanding of MASLD, emphasizing its multifactorial etiology, evolving pathophysiological mechanisms, clinical progression, and therapeutic strategies, including emerging pharmacological and lifestyle interventions. Methods: A structured review of peer-reviewed articles published between 2019 and 2025 was conducted using critical analysis of uploaded and curated literature focusing on MASLD’s pathogenesis, comorbidities, and treatment modalities. Findings: MASLD is driven by a combination of genetic, environmental, metabolic, and immunological factors. Recent insights into lipid dysregulation, gut-liver axis, immune modulation, and endocrine pathways have clarified mechanisms of disease progression. Weight loss remains a cornerstone of management, supported by emerging anti-obesity medications such as GLP-1 receptor agonists and dual agonists. Novel therapies targeting hepatic stellate cells, fibroinflammatory signaling, and microbiota-derived metabolites represent future avenues for precision-based treatment. Conclusion: Effective MASLD management necessitates an integrated approach combining lifestyle interventions, pharmacotherapy, and targeted therapeutics based on individual phenotypes. Continued research into molecular pathways and personalized strategies holds promise for disease reversal and improved patient outcomes.